Development situation and expert suggestion on "Internet+Traditional Chinese Medicine" in China - ZHANG Yu; TIAN Yang; FENG Jiajia; LIU Jiawei; ZHANG Yunling; LIN Likai; Expert Group of Current Situation and Development of "Internet + Traditional Chinese Medicine" in China (Yixue xinzhi zazhi)
Traditional Chinese medicine (TCM) is an important part of China's medical and health care system. With the development of the internet, "Internet+TCM" has become a new pattern of Chinese medicine in recent years. This study summarized the characteristics, development status, development constraints and prospects of "Internet+TCM" in China through questionnaire survey, interview and expert meeting, and puts forward expert suggestions, with a veiw to providing reference for the development of "Internet+TCM" industry in China.